2012
DOI: 10.1177/1464884912453285
|View full text |Cite
|
Sign up to set email alerts
|

The ‘new majority’ and the academization of journalism

Abstract: The academization of journalism is reliant on the development of the field founded in scholarship demonstrated through the publication of research in peer-reviewed specialist journals. Given the profile of journalism faculty, this means inducting practitioners into a culture of critical research. In Australia at least, this cohort of neophytes is predominantly comprised of middle-aged women who were surveyed about their personal attitudes to research. They were mostly open to the idea of becoming researchers b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…We might ask, then, to what extent are journalism educators perpetuating or challenging such gender preferences? Historically, journalism education has been accused of perpetuating the gender roles and disparities present in the news industry (Bromley, 2013). Future research might turn again to the contemporary gender profile of journalism departments, as well as the (often subtle) ways in which gender preferences are moulded through the curriculum.…”
Section: Discussionmentioning
confidence: 95%
“…We might ask, then, to what extent are journalism educators perpetuating or challenging such gender preferences? Historically, journalism education has been accused of perpetuating the gender roles and disparities present in the news industry (Bromley, 2013). Future research might turn again to the contemporary gender profile of journalism departments, as well as the (often subtle) ways in which gender preferences are moulded through the curriculum.…”
Section: Discussionmentioning
confidence: 95%
“…Journalism—as a research methodology—is not a ‘method’ listed in the textbooks used by most Australian universities. There is, however, an increasing body of literature (including this journal volume) that argues that it is a legitimate research method (Bacon, 1999 2006, 2012; Bromley, 2012, 2013, 2014; Davies, 2010a; Duffield, 2009; Lamble, 2004; Nash, 2014; Pearson, 2011; Pearson & Patching, 2010; Turner, 2011; Waller, 2012). Despite this, it is often difficult to get institutional support for submitting journalistic work as part of academic research output because faculty and university research committees doubt the legitimacy of journalism’s methodologies, scope of enquiry and contribution to ‘new’ knowledge.…”
Section: Journalism As Researchmentioning
confidence: 99%
“…Inevitably, that will be accompanied by a shift in relative value ascribed to journalistic and academic output. Journalist-academics must recognize the ‘publish or perish’ rules of the game they are now playing (Bromley, 2012). That is not always the case: a survey of journalist-academics found that only just over half thought that it was important for them to publish academic research at all (Harcup, 2011a).…”
Section: Academic Journalismmentioning
confidence: 99%